2009
DOI: 10.5338/kjea.2009.28.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of in vitro seed germination of Taraxacum platycarpum

Abstract: Dandelion (Taraxacum platycarpum) has been widely utilized for medicinal purposes. However, the dandelion seeds are relatively difficult to germinate under cultivation conditions, which hampers seedling propagation of dandelion plants and reduces the opportunity of usage of such a useful medicinal plant. Thus, in this study, in vitro conditions for the dandelion seed germination were optimized to enhance the germination rate. In seed washing steps, the sequential treatments with 20% of ethanol, 20% of NaOCl, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
2
4
0
Order By: Relevance
“…The osmotic effect varies directly with the presence of compounds present in the culture medium, mainly salts and sugars, the concentration of which determines the availability of water. It has been indicated that high sugar concentrations delay germination and generate abnormal seedlings [4], which is consistent with the observations of this work when high carbon SUC concentrations were studied (3.2 and 5.5%). However, the effect of sugars on germination is not only related to the osmotic pressure, since in tests with other purely osmotic compounds the response on germination is different [30,31], but both sugars modulate critical plant processes such as germination when they interact with phytohormones and PGRs [32,33].…”
Section: Effect Of Carbon Source and Pgrs On Germinationsupporting
confidence: 92%
See 3 more Smart Citations
“…The osmotic effect varies directly with the presence of compounds present in the culture medium, mainly salts and sugars, the concentration of which determines the availability of water. It has been indicated that high sugar concentrations delay germination and generate abnormal seedlings [4], which is consistent with the observations of this work when high carbon SUC concentrations were studied (3.2 and 5.5%). However, the effect of sugars on germination is not only related to the osmotic pressure, since in tests with other purely osmotic compounds the response on germination is different [30,31], but both sugars modulate critical plant processes such as germination when they interact with phytohormones and PGRs [32,33].…”
Section: Effect Of Carbon Source and Pgrs On Germinationsupporting
confidence: 92%
“…This was the result of having performed the experiment in an agar matrix instead of the traditional wet disc paper on a Petri dish or in soil pots; therefore, gas and mass transfer interactions need to be considered. Only one work reported the use of an agar matrix for T. platycarpum seed germination [4] with FGP values in agreement with those obtained in this study. However, another study in soil indicates 60% of germination for this species, so the difference between agar matrix and soil, might be important but not conclusive.…”
Section: Germination Capacity Uniformity and Synchronysupporting
confidence: 90%
See 2 more Smart Citations
“…Keeping in view low germination and difficulties in establishment of seedling due to pathogens, in vitro germination of P. marsupium can be utilized as an essential prerequisite for production en masse. Ahmad et al (2012) used MS, B5 (Gamborg et al, 1968) and White (1963) medium for in vitro seed germination of Pterocarpus marsupium without considering the seed orientation, which is an important and key factor for in vitro (Lee et al, 2009) and ex vitro (Swaminathan et al, 1993;Bhat, 2011) seed germination. Besides, they did not produce any plant through in vitro method.…”
Section: Introductionmentioning
confidence: 99%